ANALISIS PROGRAM PEMBERDAYAAN USAHA MIKRO DINAS PERDAGANGAN KOTA SURABAYA DALAM PENINGKATAN EKONOMI - Saifuddin Afif; Sri Umiyati (Faculty of Social and Political Science, 2022)
Analysis of the Surabaya City Trade Office's Micro Business Empowerment Program in Improving the Economy of Micro Business Actors Case Study on Selendang Semanggi Micro Business, Sambikerep District, Surabaya City in 2019. Etymologically empowerment comes from the basic word